2002
DOI: 10.1097/00006123-200207000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty for Intracranial Symptomatic Vertebrobasilar Ischemia

Abstract: Intracranial posterior circulation angioplasty is effective in the reduction of stenosis and can be performed with relative safety. Angioplasty can be considered as a treatment option in patients with recurrent ischemic symptoms despite medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] In the present study, TAS for occluded lesions was shown to be technically feasible with a high success rate, similar to treatment of stenotic lesions. Technical success in treating the occluded lesion depends on the freshness of the occluded clots and the occluded segment being short enough for the microguidewire to pass through it; such conditions are frequently encountered in the acute stroke stage.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10] In the present study, TAS for occluded lesions was shown to be technically feasible with a high success rate, similar to treatment of stenotic lesions. Technical success in treating the occluded lesion depends on the freshness of the occluded clots and the occluded segment being short enough for the microguidewire to pass through it; such conditions are frequently encountered in the acute stroke stage.…”
Section: Discussionsupporting
confidence: 54%
“…The procedure-related complication rate in the present study was higher than the reported rates in previous studies performed mainly for stenotic lesions and in the chronic stroke stage. [2][3][4][5][6][7][8][9][10] This may be because TAS for occluded lesions tends to induce distal embolism, intracranial hemorrhage involving hemorrhagic transformation and cerebral hyperperfusion syndrome, and vessel injury or rupture in comparison with the treatment of stenotic lesions. Because distal embolism tends to occur for a lesion crossed by a microguidewire, balloon catheter, or stent and is especially common with occluded lesions, the use of an embolic protection device with proximal flow control may reduce the incidence of this complication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with symptomatic or asymptomatic, severe intracranial atherosclerotic stenosis who were at high risk for stroke or death were included (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Intracranial Angioplasty and Stentingmentioning
confidence: 99%
“…Gress et al published the results of intracranial angioplasty in 25 patients for symptomatic vertebrobasilar ischemia in whom medical therapy had failed (30). Angioplasty was effective in reducing the degree of stenosis by Ͼ40% in all 25 vessels.…”
Section: Literature Reviewmentioning
confidence: 99%